Physico - Chemical and Biological Water Quality Analyses of Meenachil River, Kottayam, Kerala, South India - Radhika, R.; Mathew, Sojomon; Prasad, Sreelakshmi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The Meenachil River is one of the major rivers that flows through the Kottayam District of Kerala, India. The water quality of the Meenachil River was studied. Five locations of the river were chosen. pH, Turbidity, Conductivity, Hardness, Calcium & Magnesium hardness, TDS, Calcium, Magnesium, Iron, Sulphate, Chloride, Fluoride, Nitrite, Nitrate, and DO were measured. From the study, it was observed that diverse human activities have an impact on the water quality of the Meenachil River. The present study showed that the pH of the water samples rose at several places, with sample 2 taken from Erattupetta having the lowest pH, indicating that the water sample 2 is acidic in nature. Due to the discharge of industrial and household wastewater, station 5 Kottayam has the highest conductivity, hardness, alkalinity, chloride, fluoride, nitrite, nitrate, TDS, and coliform count. Dissolved oxygen was extremely low in Kottayam region.